2017
DOI: 10.4212/cjhp.v70i2.1642
|View full text |Cite
|
Sign up to set email alerts
|

Nasal-Swab Results for Methicillin-Resistant Staphylococcus aureus and Associated Infections

Abstract: Background: Nasal-swab screening for methicillin-resistant Staphylo coccus aureus (MRSA) has a quicker turnaround time than other bacterial culture methods, with results available within 24 h. Although MRSA nasal-swab screening is not intended to guide antimicrobial therapy, this method may give clinicians additional information for earlier tailoring of empiric antimicrobial agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
(35 reference statements)
0
17
0
Order By: Relevance
“…The sensitivity was 58.3% (95% confidence interval [CI] 28.6%-83.5%), specificity was 93.9% (95% CI 90.0%-96.3%), positive predictive value 30.4% (95% CI 14.1%-53.0%), negative predictive value 98.0% (95% CI 95.1%-99.3%). 15 Colonization with these organisms serves as an important risk factor for invasive infections. In our study septicemia was present in 67.8% of positive NIS samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity was 58.3% (95% confidence interval [CI] 28.6%-83.5%), specificity was 93.9% (95% CI 90.0%-96.3%), positive predictive value 30.4% (95% CI 14.1%-53.0%), negative predictive value 98.0% (95% CI 95.1%-99.3%). 15 Colonization with these organisms serves as an important risk factor for invasive infections. In our study septicemia was present in 67.8% of positive NIS samples.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also reported utilization of prediction of ESBL and MRSA infection from colonisation. 3,4,15 It is very critical to judge colonization from infection as inflammatory changes among immunocompromised is minimal. Carriage or colonization with normal commensal can prove lethal to these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there has been little literature published examining the performance of nasal MRSA screening for MRSA IAIs 9–12 . Although other studies have found high negative predictive values (NPV) of nasal MRSA screening for MRSA IAIs, the majority of this research did not occur in a critically ill population or only examined post‐surgical site infections 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the NPV of MRSA nasal screening for MRSA wound infections was shown to be far lower than the NPV for MRSA pneumonia (7). Rioux et al (7) studied nasal swab screening for MRSA in predicting MRSA bloodstream, wound, and respiratory infections in 273 inpatients where the prevalence of MRSA infection in the study population was a low 4.4%. The NPV of the MRSA nasal screen for all MRSA infections was 98%.…”
mentioning
confidence: 99%
“…However, the NPV of the MRSA nasal screen specific for MRSA wound infections was only 71%. Consequently, MRSA nasal screening seems to be more valuable in regard to allowing for de-escalation or confirmation of need for continued MRSA therapy in patients with pneumonia than in those with wound infections (5,7).…”
mentioning
confidence: 99%